2018
DOI: 10.2188/jea.je20160144
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Self-monitoring Device for Urinary Sodium-to-Potassium Ratio on Dietary Improvement in Free-Living Adults: a Randomized Controlled Trial

Abstract: BackgroundReducing the urinary sodium-to-potassium ratio is important for reducing both blood pressure and risk of cardiovascular disease. Among free-living Japanese individuals, we carried out a randomized trial to clarify the effect of lifestyle modification for lowering urinary sodium-to-potassium ratio using a self-monitoring device.MethodsThis was an open, prospective, parallel randomized, controlled trial. Ninety-two individuals were recruited from Japanese volunteers. Participants were randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Base on the previous studies, a urinary Na/K molar ratio of 1.0 may be a target level [14]. Measurement of the casual urine Na/K ratio also has the potential for providing prompt feedback to individuals using a selfmonitoring device [32]. However, it seemed difficult for Chinese participants to achieve the target level of Na/K ratio recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Base on the previous studies, a urinary Na/K molar ratio of 1.0 may be a target level [14]. Measurement of the casual urine Na/K ratio also has the potential for providing prompt feedback to individuals using a selfmonitoring device [32]. However, it seemed difficult for Chinese participants to achieve the target level of Na/K ratio recommended.…”
Section: Discussionmentioning
confidence: 99%
“…This device measures urinary Na/K ratio by the ion electrode method and displays the result within one minute. Since this device provides prompt onsite feedback in personal use, it became evaluated in randomized control trial with a view to support an individual approach for Na reduction and K increase [ 72 ]. With regard to the individual approach, it is important that there is a balance between lower effort and financial burden in order to achieve an effective intervention.…”
Section: Self-monitoring Of the Urinary Na/k Ratiomentioning
confidence: 99%
“…A recent study that examined this self-monitoring device reported finding a trend for larger reductions in the urinary Na/K ratio in a self-monitoring group under a pure self-management setting. When the baseline urinary Na/K molar ratio level was approximately 3.7, the reductions in the urinary Na/K molar ratio were 0.55 in the intervention group and 0.06 in the control group [ 72 ]. However, the intervention effect size was limited due to the lack of an effective education program for reducing the Na/K ratio.…”
Section: Self-monitoring Of the Urinary Na/k Ratiomentioning
confidence: 99%
“…Epidemiological studies have suggested that the urinary Na/K ratio is a better measurement of dietary Na reduction and K increase in relation to BP and CVD risk assessments than separate Na or K levels [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Additionally, the former is easier to measure than the latter, due to its independence from urine collection and creatinine measurement; indeed, repeated Na/K ratio measurements from spot urine samples provide more reliable estimates than those from 24-h urine samples [ 28 , 29 , 30 ]. Previous studies have demonstrated that single spot urine samples can be used to estimate the population mean values of the 24-h urine Na/K ratio [ 28 ], and that four to seven repeated measurements of the Na/K ratio in spot urine samples can be used to estimate the 24-h urine Na/K ratio in individuals [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%